Breaking down walls, weaving nets: an analysis of the mandala curriculum of the Escola Municipal Polo de Educação Integrada (Research, Society and Development, 2021)
Understanding the need to understand integral education as a teaching modality that, even being discussed since the end of the last century, still brings some doubts about its characterization, this study aims to make a qualitative documentary analysis of the curriculum proposal of the Municipal School Pole of Integrated Education (EMPOEINT), located in the city of Belo Horizonte, Minas Gerais. The school's proposal places the subject as its starting point and, therefore, aims at his/her integral formation. In this sense, the notion of integral education becomes a central point in the curriculum proposal of EMPOEINT and can be a good example to help clarify hazy aspects of the aforementioned understanding. In this sense, a qualitative study of the documental kind was carried out, in which documents that govern the national education were analyzed, in order to build a cut about the integral education in the country and after, the Pedagogical Political Project of the school, bringing an interpretive-descriptive analysis to highlight unique characteristics of the curricular proposal of the school in question, the curriculum-mandala. From the analysis, it is believed that the curriculum-mandala allows the student to find in school a passage, an endless path of construction and deconstruction of knowledge, taking as method the movement brought in the title of this work: breaking down walls, weaving networks.